2019
DOI: 10.1002/ange.201903259
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Halogen‐Bonding‐Driven 3D Supramolecular Assembly of Right‐Handed Synthetic Helical Peptides

Abstract: Peptide-mediated self-assembly is ap revalent method for creating highly ordered supramolecular architectures.H erein, we report the first example of orthogonal CÀ X···XÀC/CÀX···p halogen bonding and hydrogen bonding driven crystalline architectures based on synthetic helical peptides bearing hybrids of l-sulfono-g-AApeptides and natural amino acids.T he combination of halogen bonding, intra-/intermolecular hydrogen bonding,a nd intermolecular hydrophobic interactions enabled novel 3D supramolecular assembly.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Besides inhibiting the p53–hDM2 interactions, β 3 -peptide has also been developed to serve as HIV fusion inhibitors. They further developed a β 3 -decapeptide with a non-natural trifluoromethylbenzene side chain that inhibited the HIV gp41-mediated fusion with a CC 50 /EC 50 ratio of 8, a major improvement compared to previous works. , Cai et al developed an impressive class of sulfono-γ-AApeptides that can reproducibly fold into well-defined helical structures. They demonstrated that these sulfono-γ-AApeptide helices were excellent mimicries of α-helices in several therapeutically relevant protein–protein interactions and could serve as inhibitors or agonists to these interactions, such as BCL9-β-catenin, p53-MDM2/MDMX, and glucagon peptide-GLP-1R. …”
Section: Functional Applications Of Sequence-controlled Polymersmentioning
confidence: 99%
“…Besides inhibiting the p53–hDM2 interactions, β 3 -peptide has also been developed to serve as HIV fusion inhibitors. They further developed a β 3 -decapeptide with a non-natural trifluoromethylbenzene side chain that inhibited the HIV gp41-mediated fusion with a CC 50 /EC 50 ratio of 8, a major improvement compared to previous works. , Cai et al developed an impressive class of sulfono-γ-AApeptides that can reproducibly fold into well-defined helical structures. They demonstrated that these sulfono-γ-AApeptide helices were excellent mimicries of α-helices in several therapeutically relevant protein–protein interactions and could serve as inhibitors or agonists to these interactions, such as BCL9-β-catenin, p53-MDM2/MDMX, and glucagon peptide-GLP-1R. …”
Section: Functional Applications Of Sequence-controlled Polymersmentioning
confidence: 99%
“…Peptidomimetics include peptoids, β-peptides, and γ-peptides that were able to bind to different biomarkers of diseases such as Alzheimer’s, Parkinson’s, and AIDS . Recently, sulfono-γ-AA peptides were developed to function as either agonists or antagonists. These can mimic α-helices in therapeutically relevant protein–protein interactions, due to their highly reproducible folding capacity. …”
Section: Sequence-controlled Polymersmentioning
confidence: 99%
“…Sulfono--AApeptides are recently introduced as a new class of helical mimetics to address some enduring challenges in disrupting -helix-mediated protein-protein interactions (20)(21)(22)(23)(24)(25)(26)(27). As proteolytically stable peptidomimetics, sulfono--AApeptides exhibit unusual folding stability by adopting a series of helical structures with well-defined hydrogen bonding patterns (21).…”
Section: Introductionmentioning
confidence: 99%